Perlindungan Hukum bagi Nasabah atas Praktek Penagihan Angsuran Kredit Tanpa Pencatatan Petugas Bank: Studi pada Bank Mekar Bima - Raodatul Jannah; Iksan Iksan; Kasmar Kasmar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines legal protection for customers regarding the practice of credit installment collection without recording by Bank Mekar Bima officers. Collection practices that are not accompanied by official recording can cause losses for customers, such as the occurrence of credit installment arrears. This study aims to determine and analyze the mechanism of credit installment collection carried out by bank officers according to applicable legal provisions, as well as examine the form of legal protection for customers regarding the practice of credit installment collection without recording by Bank Mekar Bima officers. The results of the study indicate that there are indications of collection practices that are not accompanied by official recording evidence, resulting in complaints from customers regarding their payment status. Because proof of payment that should be the basis for legal accountability is not legally documented.